Dust material and mathematical relationship identification for photovoltaic systems - Maghami, Mohammad Reza (2015)
Photovoltaic (PV) systems are one of the next generation’s renewable energy sources for our world energy demand. PV modules are highly reliable. However, in polluted environments, over time, they will collect grime and dust. There are also limited field data studies about soiling losses on PV modules. This study is to investigate the effect of accumulated dust material on PV performance. The study includes two arrays of mini-modules. Each array has 12 PV modules tilted at 15º on the ground. The first array called "cleaned" was cleaned every week. The second array called "dusty" was never cleaned since the first day. Three types of data were required. The first type of data related to PV electrical characteristics. The second type related to environmental conditions, and the last type was associated with dust materials analysis. Required data were collected for eight months from April until first of December 2013. Due to a fault in the system, for 38 days there was no record of data and the final record was for a total of 209 days. Data from PV array and environmental data were collected with an online monitoring system and recorded every one minute over eight months. The data were analyzed to investigate the effect of dust on daily and monthly soiling, as well as transmitted solar insolation and energy production by PV modules. The main objective of this research is to conduct an experimental investigation on the effect of dust accumulated on the surface of PV array on output power in an open area where the effect of dust is unavoidable. For purposes of improvement, a mathematical relationship was predicted for the dust effect on PV generator performance. A comparative analysis was conducted to evaluate the effect of dust on PV array performance. The study shows that during the period of April through December 2013 there was an average loss due to soiling, of approximately 2.83% on dusty array. Comparing these two arrays for different months also was done and the results show that there are significant differences of output power among different months between the two arrays. Scatter plot was also employed for output power and environmental data to assess the relationship between the amount of output power generated from the dusty array and irradiation. The result shows that there was a positive correlation between the output power and irradiation variables, Correlation coefficient between thickness and power output indicated a moderate and negative relationship. Two mathematical relationship were predicted despite the dust thickness for dusty array and without dust, thickness for clean array and the validation of both prediction models was evaluated.